ANALISIS KEAKURATAN KODIFIKASI DIAGNOSIS TERHADAP KUALITAS LAPORAN MORBIDITAS RAWAT JALAN (RL 4b) DI RUMAH SAKIT UMUM HERMINA PASTEUR BANDUNG - Hopsah, Eva (Jurnal Infokes, 2023)
The guidelines for writing major diagnoses have an impact on how they are coded; each diagnostic statement must be clear and informative in order to place the disease in the ICD-10 category with the highest level of specificity. The accuracy of the diagnosis, the readability of the doctor’s writing, the professionalism of the doctor and the coding, and other factors all influence the quality of the coding findings. The literature review was used as the research design. The codification analysis has not been carried out ideally so that there is still inaccurate code and makes the reports that have been made less accurate and seen from the preparation and delivery of reports that have been carried out on time so that the level of relevance of the report is 92%. Research analysis on the accuracy of codification of diagnoses on the quality of outpatient morbidity reports (RL 4b), based on a sample of 100 medical records examined, 100 medical records that were accurate 60 or 60% and 40 medical records that were inaccurate or 40%, Reliability test results with using the Cronbachs Alpha method with a significance level of 10% (0.1), namely 0.923, was then taken into consideration. This value is greater than the r table value of 0.4409 which indicates that the reliability test was successful and the questionnaire results are reliable. .Keywords: Codification; diagnosis; Medical records